(untitled) (Bangladesh Journal of Medical Science, 2019)
Background: Morel-Lavallée Lesion (MLL) or Morel-Lavallée Seroma (MLS) is a posttraumatic seroma that occurs following a closed degloving injury. It is very important for trauma surgeons to be aware of this relatively rarely reported entity as early diagnosis increases the likelihood of successful management. Case report: We present a patient, wherein the patient had no history of trivial trauma and presented with a gradually growing swelling of left thigh, that was clinically and radiologically diagnosed as a soft tissue neoplasm, successfully managed by surgical excision and were reported to be a MLS. The clinical diagnostic dilemma was solved by the histopathologist! Conclusion: A differential diagnosis of MLL should be kept in mind in patients presenting with soft tissue swellings. Bangladesh Journal of Medical Science Vol.18(1) 2019 p.145-148